KEAUTENTIKAN AKIDAH AHLUS SUNNAH: Pembuktian Keotentikan Melalui Sejarah Pembukuan Akidah Ahlus Sunnah - Abdullah Zaen; Gufron Nulailan Thawila; Winning Son Ashari (Al-Majaalis : Jurnal Dirasat Islamiyah, 2023)
It is common that when someone wants to buy an item, he will try to choose the original item and avoid those labeled genuine but fake, but ironically they don't set the right standard when choosing their creed. The most valuable thing that a human has is his faith, because it is the foundation of his religion and determines whether or not the practice he does is accepted. However, it is very unfortunate that not a few among the Muslims are less concerned with the authenticity of the creed that they believe in. As for one group that the Prophet sallallaahu 'alaihi wasallam has guaranteed to be safe from the fires of hell they are ahlus sunnah wal jama'ah, of course the creed they adhere to is the original creed, which was passed down by the Prophet sallallaahu 'alaihi wasallam. There are people who claim they are ahlus sunnah wal jama'ah, but they do not know the indicators of the authenticity of the ahlus sunnah wal jama'ah belief. Among the objectives of this research is to find out what are the indicators of the authenticity of the ahlus sunnah wal jama'ah beliefs, and how to prove the authenticity of the ahlus sunnah beliefs through the history of bookkeeping. Researchers used a literature review approach with a qualitative descriptive method. The results of the study show that the authenticity of the ahlus sunnah wal jama'ah beliefs are: a.) Based on the Al-Qur'an and Hadith, b.) Principled surrender to Allah and His Messenger, c.) In accordance with nature and common sense, d.) The chain goes to the Prophet sallallaahu 'alaihi wasallam, e.) Clear and obvious, f.) Continue to exist until the Day of Judgment, g.) unifying the people, h.) Guarantee of safety and glorious life from Allah. Proving the authenticity of the ahlus sunnah wal jama'ah beliefs through the history of bookkeeping which is proof that the chain of ahlus sunnah wal jama'ah beliefs continues from time to time.